Research on the influence of sports participation on school bullying among college students—Chain mediating analysis of emotional intelligence and self-esteem - Yiyi, Ouyang; Jie, Peng; Jiong, Luo; Jinsheng, Teng; Kun, Wang; Jing, Li (Frontiers in Psychology, 2022)
Purposes: This paper aims to discuss the relationship among college students' sports participation, emotional intelligence, self-esteem and school bullying, at the same time explore school bullying’s the intrinsic mechanism in order to provide references for reducing bullying behavior among college students, thus providing college students a healthy, confident and optimistic living habits. Methods: Students from four universities in Southwest China were selected as the subjects of investigation. They were selected by stratified random sampling, and the data were processed by SPSS19.0 and AMOS21.0 statistical software. Results: 1) Sports participation has significant and positive correlated with emotional intelligence and self-esteem, it is also significantly related to the negative correlation with school bullying; emotional intelligence is notable and positively correlated with self-esteem, at the same time it is markedly negative correlated with school bullying; in addition, self-esteem is also strongly negative correlated with school bullying; 2) Sports participation has a direct effect on school bullying (ES=- 0.271); emotional intelligence (ES=-0.144) and self-esteem (ES=-0.065) play a significant mediating role between sports participation and school bullying, the chain mediating force of emotional intelligence - self-esteem also reaches a significant level (ES=-0.016). Conclusion: Sports participation can affect the display of school bullying among college students not only directly but also indirectly, such as through emotional intelligence, the mediating role of self-esteem, and the chain mediating role of emotional intelligence to self-esteem. Apart from sports participation, emotional intelligence is another key factor that affects college students' school bullying behavior. Therefore, while the school attaches great importance to the college students' sports participation, it is also necessary to open some courses for the purpose of developing their emotional intelligence.